2017
DOI: 10.1038/s41598-017-07588-9
|View full text |Cite
|
Sign up to set email alerts
|

Shape dependent cytotoxicity of PLGA-PEG nanoparticles on human cells

Abstract: We investigated the influence of nanoparticles’ shape on the physiological responses of cells, when they were fed with spherical and needle-shaped PLGA-PEG nanoparticles (the volume of the nanoparticles had been chosen as the fixed parameter). We found that both types of NPs entered cells via endocytosis and upon internalization they stayed in membrane bounded vesicles. Needle-shaped, but not the spherical-shaped NPs were found to induce significant cytotoxicity in the cell lines tested. Our study evidenced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 36 publications
2
58
0
4
Order By: Relevance
“…1C). Experimental evidence showed that the spherical shape of the NPs has extended cellular uptake via endocytosis compared to the needle-shaped [23]. …”
Section: Resultsmentioning
confidence: 99%
“…1C). Experimental evidence showed that the spherical shape of the NPs has extended cellular uptake via endocytosis compared to the needle-shaped [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Uncoated silicon‐based particles showed distinct shape‐dependent biodistribution upon intravenous injection, with discoidal particles accumulating significantly more in the lungs compared to their spherical, cylindrical, and hemispherical counterparts, whereas liver accumulation was much higher for cylindrical particles compared to the rest . Shape has also been implicated in altering cell‐specific responses to nanoparticles, especially uptake, but also viability and cytoskeletal organization …”
Section: Introductionmentioning
confidence: 99%
“…Проведенные ранее эксперименты позволили предположить, что при умеренном перенасыщении крови ионами кальция и фосфора могут образовываться КФБ сферической формы, а REVIEW ARTICLE ФУНДАМЕНТАЛЬНАЯ И КЛИНИЧЕСКАЯ МЕДИЦИНА ® при тяжелом перенасыщении -КФБ игольчатой формы [68,69]. При этом известно, что форма наночастиц гидроксиапатита является одним из основных факторов, определяющих их токсичность; в частности, наночастицы игольчатой формы значительно токсичнее сферических [70][71][72], причем данная зависимость также характерна и для других типов наночастиц, не являясь специфичной для гидроксиапатита или форм фосфата кальция в целом [73]. Токсичность кристаллов гидроксиапатита определяется в том числе другими физико-химическими параметрами, такими как размерность [69,70,74], степень кристалличности [75], площадь поверхности [76], соотношение продольного и поперечного диаметров [76], а также наличие или отсутствие белковой оболочки [59].…”
Section: физико-химические свойства кфб и их связь с их патогенными эunclassified